Population structure, adaptation and divergence of the meadow spittlebug, Philaenus spumarius (Hemiptera, Aphrophoridae), revealed by genomic and morphological data - Seabra, Sofia G. (2022)
Understanding patterns of population differentiation and gene flow in insect vectors of plant diseases is crucial for the implementation of management programs of disease. We investigated morphological and genome-wide variation across the distribution range of the spittlebug Philaenus spumarius (Linnaeus, 1758) (Hemiptera, Auchenorrhyncha, Aphrophoridae), presently the most important vector of the plant pathogenic bacterium Xylella fastidiosa Wells et al., 1987 in Europe. We found genome-wide divergence between P. spumarius and a very closely related species, P. tesselatus Melichar, 1899, at RAD sequencing markers. The two species may be identified by the morphology of male genitalia but are not differentiated at mitochondrial COI, making DNA barcoding with this gene ineffective. This highlights the importance of using integrative approaches in taxonomy. We detected admixture between P. tesselatus from Morocco and P. spumarius from the Iberian Peninsula, suggesting gene-flow between them. Within P. spumarius, we found a pattern of isolation-by-distance in European populations, likely acting alongside other factors restricting gene flow. Varying levels of co-occurrence of different lineages, showing heterogeneous levels of admixture, suggest other isolation mechanisms. The transatlantic populations of North America and Azores were genetically closer to the British population analyzed here, suggesting an origin from North-Western Europe, as already detected with mitochondrial DNA. Nevertheless, these may have been produced through different colonization events. We detected SNPs with signatures of positive selection associated with environmental variables, especially related to extremes and range variation in temperature and precipitation. The population genomics approach provided new insights into the patterns of divergence, gene flow and adaptation in these spittlebugs and led to several hypotheses that require further local investigation.